2009
DOI: 10.1590/s0100-879x2009000700012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation procedures affect the center of pressure frequency analysis

Abstract: Even though frequency analysis of body sway is widely applied in clinical studies, the lack of standardized procedures concerning power spectrum estimation may provide unreliable descriptors. Stabilometric tests were applied to 35 subjects (20-51 years, 54-95 kg, 1.6-1.9 m) and the power spectral density function was estimated for the anterior-posterior center of pressure time series. The median frequency was compared between power spectra estimated according to signal partitioning, sampling rate, test duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…Based on these findings, it can be assumed that the results of the CoP measurements become more stable with increasing measurement time and are subject to less fluctuation [6]. The investigations of Vieira et al also arrived at a similar conclusion [7]. In line with this, van der Kooij et al (2011) showed that with a shorter measurement time, the results of the frequency-dependent parameters are larger.…”
Section: Influence Of Measurement Time and Frequencymentioning
confidence: 79%
“…Based on these findings, it can be assumed that the results of the CoP measurements become more stable with increasing measurement time and are subject to less fluctuation [6]. The investigations of Vieira et al also arrived at a similar conclusion [7]. In line with this, van der Kooij et al (2011) showed that with a shorter measurement time, the results of the frequency-dependent parameters are larger.…”
Section: Influence Of Measurement Time and Frequencymentioning
confidence: 79%
“…Future work should seek to confirm this value as the most appropriate for a cut-off level. In addition, it has been suggested that the majority of the power in the COP spectrum lies within a range of DC to between 1.00-1.40 Hz, depending on the measurement methodology (Vieira et al, 2009). Therefore, the highest frequency range analyzed (1.60-3.20 Hz), although statistically different between groups, may have limited practical significance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies analyze the frequency content of the whole measurement using Power Spectral Density (PSD) [12,13,20]. These studies often examine the median frequency (MDF) [21,22], mean power frequency (MPF) [15,20,23] and bandwidth (BW) [15,23] of the CoP signals in AP and ML directions. Further analyses concern the power ratios of different frequency bands on the power spectrum of CoP signals, revealing differences in the frequency content of eyes closed and eyes open bilateral standing conditions in people with multiple sclerosis [24] or in athletes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Further analyses concern the power ratios of different frequency bands on the power spectrum of CoP signals, revealing differences in the frequency content of eyes closed and eyes open bilateral standing conditions in people with multiple sclerosis [24] or in athletes [5]. Many frequency-related posturographic parameters are highly sensitive to acquisition settings [25] and parameter settings of the different spectral estimators [21], with a resulting diversity in the results of the same measurements among different studies. Thus suggestions of standardized measurements and processing [21,25] as well as minimal acquisition criteria have been reported [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation